2002
DOI: 10.1051/0004-6361:20011553
|View full text |Cite
|
Sign up to set email alerts
|

An $\ion{H}{i}$ survey of the Centaurus and Sculptor groups

Abstract: Abstract. We present results of two 21-cm H i surveys performed with the Australia Telescope Compact Array in the nearby Centaurus A and Sculptor galaxy groups. These surveys are sensitive to compact H i clouds and galaxies with H i masses as low as ∼3 × 10 6 M , and are therefore among the most sensitive extragalactic H i surveys to date. The surveys consist of sparsely spaced pointings that sample approximately 2% of the groups' area on the sky. We detected previously known group members, but we found no new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 24 publications
5
37
0
Order By: Relevance
“…Prior evidence for preprocessing of the gas content in the group environment comes from estimates of the H I mass function (HIMF) which historically have been derived from individual groups or small group samples (e.g. Verheijen et al 2000;de Blok et al 2002;Kovac et al 2005;Freeland et al 2009;Kilborn et al 2009;Pisano et al 2011;Hess 2011). Despite the small number statistics, calculations of the group HIMF reliably suggest a flatter slope at the low mass end than the field or global HIMF.…”
Section: Halo Occupation Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior evidence for preprocessing of the gas content in the group environment comes from estimates of the H I mass function (HIMF) which historically have been derived from individual groups or small group samples (e.g. Verheijen et al 2000;de Blok et al 2002;Kovac et al 2005;Freeland et al 2009;Kilborn et al 2009;Pisano et al 2011;Hess 2011). Despite the small number statistics, calculations of the group HIMF reliably suggest a flatter slope at the low mass end than the field or global HIMF.…”
Section: Halo Occupation Distributionmentioning
confidence: 99%
“…In any case, population studies derived from small samples of groups consistently show that the group H I mass function (HIMF) is flatter than the global HIMF, revealing either a paucity of low gas-mass galaxies or simply hinting that denser environments are harsh on low gas-mass galaxies (Verheijen et al 2000;de Blok et al 2002;Kovac et al 2005;Freeland et al 2009;Kilborn et al 2009;Pisano et al 2011;Hess 2011). While Freeland et al (2009) found that groups with a mix of morphological types exhibit more signs of recent tidal interactions than groups dominated by one morphological type.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the Local Group and the Sculptor Group appear to form a filament of galaxies, rather than two unique groups (e.g., Jerjen et al 1998), the bias in the clouds distribution toward the southern and closest part of the group could actually be an extension of a population of Local Group intergalactic H i clouds in the direction of the closest group to the Local. This explanation places the detected clouds closer and makes them less massive (generally under 6 Â 10 6 M at 1 Mpc), leaving the nondetection in the northern half of the Sculptor Group and other groups open to further speculation (e.g., de Blok et al 2002;Zwaan 2001;Banks et al 1999). Although the diffuse connections between the clouds was used to argue for a closer origin above, extended H i at lower column densities might also be expected if the clouds are the equivalent of the Ly absorbers along filaments of galaxies.…”
Section: Relationship To the Sculptor Group Galaxies?mentioning
confidence: 99%
“…Zwaan (2001) andde Blok (2002) made incomplete samplings of several galaxy groups to limits of a few × 10 6 M . Minchin et al (2003) surveyed the Cen A group to a limit of 2 × 10 6 M , and Pisano et al (2004Pisano et al ( , 2007 observed six Local Group analogs to (2-5) ×10…”
Section: Previous H I Surveys and Comparison With Ngc 2903mentioning
confidence: 99%